Mechanisms of methanol detection in graphene oxide and conductive polymer active layers for gas sensing devices - das Neves, Matheus F. F.; Mukim, Shardul; Ferreira, Mauro S.; Roman, Lucimara S. (Frontiers in Carbon, 2024)
The admixture of PEDOT:PSS with Graphene Oxide (GO) in precise proportions achieves a substantial reduction in electrical resistivity, thereby augmenting its suitability as an electrode in organic devices. This study explores the electrical and morphological attributes of commercial PEDOT:PSS and chemically synthesized aqueous PEDOT ink when both are combined with GO. The investigation extends to the application of these conductive inks as active layers in flexible methanol sensing devices. Notably, a resistivity minimum is observed in the case of GO:PEDOT:PSS 78%, while the highest response to methanol is attained with GO:PEDOT:PSS 68%. To establish a theoretical underpinning for these findings, and to understand the interaction between gas/vapors with nanostructured materials, a model rooted in Kirchhoff's Circuit approach is developed, with the aim of elucidating the factors behind the resistivity minimum and response maximum at distinct specific mass ratios between PEDOT and GO. Calculating the equivalent resistivity and response of the systems, the positions of minimum and maximum points are in agreement with the experimental data. Furthermore, the influence of PSS in the samples is examined, unveiling diverse interaction mechanisms between methanol molecules and the active layer, resulting in varying signals during the exposure to alcoholic vapor. The theoretical model is subsequently applied to these systems, demonstrating qualitative and quantitative agreement with the experimental results.